2011
DOI: 10.1017/s0022112010006257
|View full text |Cite
|
Sign up to set email alerts
|

On two-dimensional foam ageing

Abstract: International audienceThe present study aims at documenting, making use of an original set-up allowing to acquire well-converged data, the coarsening of foams in two dimensions. Experiments show that a foam behaves quite differently depending on the way it has been prepared. We distinguish between an initially quasi-monodisperse foam and a polydisperse foam. The coarsening laws are initially different, although both foams reach a common, time-dependent asymptotic regime. The ageing process relies on exchanges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…From all runs, a total of 14 663 bubbles were observed. This is enough for statistical purposes, though it is possible to observe many more bubbles at lower resolution using sample cells that are larger or have thinner gaps [43,44].…”
Section: Methodsmentioning
confidence: 99%
“…From all runs, a total of 14 663 bubbles were observed. This is enough for statistical purposes, though it is possible to observe many more bubbles at lower resolution using sample cells that are larger or have thinner gaps [43,44].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Roth et al [16] have recently reported detailed investigations into the coarsening behaviour of such quasi-2D foams with different liquid fractions. Duplat et al did an extensive study of the evolution of a 2D monodisperse foam towards the scaling state through coarsening [28].…”
Section: Introductionmentioning
confidence: 99%
“…The geometrical disorder is the relative width of the bubble size distribution; it is fixed by the repartition of gas between bubbles, and it plays a role in a foam's mechanical properties [3]. The topological disorder is the relative width of the bubble side number distribution; it is determined by the past history of the foam, and it plays a role in foam coarsening [4].…”
Section: Introductionmentioning
confidence: 99%